Comparison of the various diagnostic criteria used in polycystic ovary syndrome - Singh, Neha; Hooja, Nupur; Yadav, Angela; Bairwa, Pooja; Jaiswal, Aditi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Polycystic Ovary Syndrome (PCOS) represents one of the major causes of infertility in women. Various criteria are set to diagnose PCOS, some over diagnose and some underdiagnose it. The objective of the study was to compare the various criteria used for the diagnosis of PCOS: NIH 1990 criteria, Rotterdam 2003 criteria and AE-PCOS Society 2006 criteria. Methods: This was a cross-sectional study conducted over a period of one year. Patients with suspicion of PCOS were selected. After complete history and examination, blood samples were collected and androgen levels were measured. They were labeled as PCOS based on their fulfillment of the criteria as per Rotterdam, NIH and AE-PCOS Society.Data was analysed and conclusions drawn. Results: Of the participants, 25.7%, 28.5%, and 62.8% were diagnosed with PCOS using NIH, AE-PCOS Society, and Rotterdam criteria, respectively. Phenotypes that included hyperandrogenism and/or hyperandrogenemia as part of their criteria showed increase in values of DHEAS and S. testoterone as compared to the normoandrogenic phenotype included in only the Rotterdam criteria. Conclusions: It is crucial to establish the diagnostic criteria for PCOS and initiate early treatment as this may play a role in the prevention of metabolic and cardiovascular diseases.